A Behavioral Lifestyle Intervention to Limit Gestational Weight Gain in Pregnant Women with Overweight and Obesity. Issue 4 (22nd February 2021) - Liu, Jihong; Wilcox, Sara; Wingard, Ellen; Turner‐McGrievy, Gabrielle; Hutto, Brent; Burgis, Judith
Abstract : Objective: This study aimed to evaluate the effects of an antenatal behavioral lifestyle intervention on total gestational weight gain (GWG) and perinatal outcomes. Methods: Pregnant women with overweight and obesity in South Carolina were recruited into a theory‐based randomized controlled trial ( n  = 112 intervention, n  = 105 standard care), which was designed to target weight self‐monitoring, increased physical activity, and improved dietary practices. Results: Participants were racially/ethnically diverse (44% African American). Intervention and standard care participants had similar total GWG at delivery (12.9 ± 6.9 vs. 12.4 ± 8.3 kg, respectively), but intervention participants had a smaller standard deviation ( P  = 0.04) in total GWG. The treatment effects were moderated by race/ethnicity and prepregnancy BMI. Among African American participants with overweight, intervention participants gained 4.5 kg less, whereas, among African American women with obesity, intervention participants gained 4.1 kg more than standard care participants. Total GWG among White participants was similar regardless of weight status and group assignment. Fewer intervention participants than standard care participants had adverse pregnancy outcomes ( P ≤ 0.01). Conclusions: The behavioral lifestyle intervention favorably impacted GWG in African American participants with overweight but not African American participants with obesity. The intervention's overall favorable impact on perinatal outcomes suggests that the mechanisms beyond total GWG may drive these outcomes.